Cyanocharax obi, a new species (Characiformes: Characidae) and the first record of the genus from tributaries of the río Paraná basin, Argentina - Casciotta, Jorge; Almirón, Adriana; Piálek, Lubomír; Říčan, Oldřich (Zootaxa, 2012)
Cyanocharax obi is described from tributaries of the arroyo Paranay–Guazú, río Paraná basin, Misiones province, Argen-tina. This new species can be distinguished from its congeneres by the following combination of characters: lateral lineinterrupted or with alternated series of perforated and non perforated scales, 22–24 branched anal-fin rays, body depth atdorsal-fin origin (34.5–40.8% SL), and distal border of anal fin in matures males nearly straight. Validity of the new spe-cies is also well supported by a molecular phylogenetic analysis (COI, 12S, 16S). Cyanocharax obi represents the first record of the genus in the río Paraná basin.